Trends in Sudden Cardiac Death Among Adults Aged 25 to 44 Years in the United States: An Analysis of 2 Large US Databases - Marco Zuin; Sanghamitra Mohanty; Rahul Aggarwal; Matteo Bertini; Behnood Bikdeli; Nada Hamade; Hannah Leyva; Andrea Natale; Giuseppe Boriani; Gregory Piazza (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Sudden cardiac death (SCD) in early adults aged 25 to 44 years represents an important and unexpected cause of death. We assessed trends in SCD‐related mortality in the United States from 1999 to 2020 among early adults to determine differences by sex, ethnoracial groups, urbanization, and census region. Methods and Results Mortality data were retrieved from the Centers for Disease Control and Prevention Wide‐Ranging Online Data for Epidemiologic Research (CDC WONDER) data set from 1999 to 2020. Age‐adjusted mortality rates were assessed using the Joinpoint regression modeling and expressed as estimated average annual percentage change with relative 95% CIs. Trends in prevalence of coronary artery disease/myocardial infarction, heart failure, and stroke, which may have contributed to SCD‐related mortality over the same period, were obtained from the National Health and Nutrition Examination Survey. From 1999 to 2020, 10 516 US early adults aged 25 to 44 years had SCD (7832 men and 2684 women), resulting in 3.72 deaths per 1000 population, or a mean of 478 deaths annually. The relative age‐adjusted mortality rate increased linearly (average annual percentage change: +1.0% [95% CI, 0.3–1.8]), without sex differences. The age‐adjusted mortality rate increase was more pronounced in Black patients, Hispanic/Latinx patients, and residents of rural areas. Higher absolute numbers of SCDs were clustered in the South (47.6%). During the same period, the prevalence of coronary artery disease/myocardial infarction, heart failure, and stroke plateaued. SCD‐related mortality associated with opioids/stimulants overdose significantly increased over the entire study period. Conclusions SCD‐related mortality among early adults has increased over the last 2 decades in the United States with notable racial and regional disparities.